Changes in Performance on Cognitive Abilities And Manual Dexterity Tasks Across Different Phases of the Menstrual Cycle - Kaur, Tavleen (My University, 2023)
Variations in Performance on various cognitive abilities, verbal memory, perceptual motor skills, etc., owing to different phases of the Menstrual Cycle, have produced mainly conflicting results in the past. Although performances of both genders overlap to a large degree (McKeever, 1995), women tend to outperform men in specific aspects of verbal ability (Halpern, 1986; McGlone, 1980), whereas men achieve higher scores in spatial tasks (Halpern, 1996; Hyde, 1981; McGee, 1979; Voyer, Voyer, & Bryden, 1995; Witkin, Dyk, Faterson, Goodenough, & Karps, 1962). The present experiment investigated Changes in Performance on Cognitive Abilities and Manual Dexterity Tasks Across Different Menstrual Cycle Phases. The data was collected from 35 female participants aged 18 to 28 years. The tools used for the purpose described above were the 3-Dimensional Space Task for Spatial Ability (a subscale in GATB), O’Connor Finger Dexterity Test, the Letter-Number Sequencing Task (a subscale of WAIS-IV), and the Wisconsin Card Sorting Test. Descriptive Statistics and Paired T-Test was computed to calculate the results for the obtained data. The results revealed that women perform better on Spatial Ability Task, Executive Functioning Task, and Working Memory Task when mensurating compared to when in the Luteal phase. In contrast, the results of Manual Dexterity were quite promising in the Luteal Phase compared to the Menstrual Phase.
Keywords: Spatial Ability; Working Memory; Automated Tasks; Menstrual Phase, and Luteal phase